Effect of Andrographis paniculata (Burm.f) Ness Herbs and Gynura Procumbens (Merr) Leaves Extracts Combination in Free-Radical Scavenging Activity - Kurnia Rahayu Purnomo Sari; Nofran Putra Pratama; Margaretha Kurniasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Development of medical plants as an alternative treatment needs support in terms of scientific evidence to increase public confidence in its efficacy and to ensure the safety of its use. Recent research on Andrographis paniculata (Burm.f) Ness dan Gynura procumbens (Lour.) Merr show that the combination of these two extracts has a potential to be developed into antihyperglycemic agent, through the mechanism of action as an antioxidant. The aim of this study was to evaluate the antioxidant effect of these two extracts combination. Extraction was done by maceration method. Testing of free radical capture activity was carried out by the DPPH method. The results of the antioxidant activity test showed that the combination of soluble ethanol extract of A. paniculata herbs and G. procumbens leaves 50:50 had the best IC50 value of 91.418 µg/mL, the combination of soluble ethanol extract 75:25 had IC50 value 117,059 µg/mL, and the combination combination of soluble ethanol extract 25:75 had the weakest IC50 of 142,277 µg/mL. The three comparisons of the combination were weaker in antioxidant activity compared to the standard vitamin C which had IC50 3,546 µg/mL. Statistical analysis using one-way ANOVA obtained significant differences in antioxidant activity of the three comparison groups.